In vitro antidiabetic potential of hydroethanolic fruit extract of pedalium murex (l) - K. SWATHI; DR. B. RAGAVAN (International Journal of Pharma and Bio Sciences, 2018)
Diabetes Mellitus is a systemic endocrine disorder with an elevated blood glucose level. These “hyperglycemic spikes” are characterized by abnormal carbohydrate, lipid and protein metabolism which may be related to the post diabetic complications. The present study evaluates the in vitro antidiabetic potential of hydroethanolic fruit extract of Pedalium murex (L). The hydroethanolic fruit extract were examined for inhibition of α-Amylase and α-Glucosidase, Glucose diffusion and Amylolysis kinetic study. There was a dose-dependent increase in percentage inhibitory activity against α-amylase and α-glucosidase and also the hydroethanolic fruit extract demonstrated significant inhibitory effects on the movement of glucose into external solution across dialysis membrane as compared to control. With further methodical studies, it can be evidenced as a beneficial source of natural antidiabetic lead compound.